2019
DOI: 10.3390/ijms20153748
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium Chloride Restores the Function of the Gap Junctional Intercellular Communication between Hepatocytes in a Liver Injury

Abstract: Background: Gadolinium chloride (GdCl3) has been reported to attenuate liver injury caused by a variety of toxicants. Gap junctional intercellular communication (GJIC) is thought to be essential in controlling liver homeostasis and pathology. Here we evaluate the effects of GdCl3 on functional GJIC and connexin expression in mouse models and primary hepatocytes. Methods: Mice were administered GdCl3 intraperitoneally the day before a carbon tetrachloride (CCl4) injection or bile duct ligation (BDL) operation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…These findings are in agreement with previous in vivo studies in rats, where lower protein levels, but a rise in mRNA was seen, albeit for Cx32 (Nakata et al 1996;Miyashita et al 1991;Cowles et al 2007). However, Yang et al (2019) recently noted a fall in Cx32 and Cx26 mRNA levels upon CCl4 administration. Despite this contradiction with earlier studies, the previously reported functional inhibition of GJIC was observed (Yang et al 2019;Nakata et al 1996).…”
Section: Carbon Tetrachloridementioning
confidence: 99%
See 4 more Smart Citations
“…These findings are in agreement with previous in vivo studies in rats, where lower protein levels, but a rise in mRNA was seen, albeit for Cx32 (Nakata et al 1996;Miyashita et al 1991;Cowles et al 2007). However, Yang et al (2019) recently noted a fall in Cx32 and Cx26 mRNA levels upon CCl4 administration. Despite this contradiction with earlier studies, the previously reported functional inhibition of GJIC was observed (Yang et al 2019;Nakata et al 1996).…”
Section: Carbon Tetrachloridementioning
confidence: 99%
“…However, Yang et al (2019) recently noted a fall in Cx32 and Cx26 mRNA levels upon CCl4 administration. Despite this contradiction with earlier studies, the previously reported functional inhibition of GJIC was observed (Yang et al 2019;Nakata et al 1996). This inhibitory effect of CCl4 is associated with cytotoxicity (Cowles et al 2007), primarily mediated by oxidative and lipid peroxidative damage indirectly triggering genotoxicity (Eastmond 2008).…”
Section: Carbon Tetrachloridementioning
confidence: 99%
See 3 more Smart Citations